Birr al-wālidayn: Studi Komparatif Penafsiran Surah al-Isrā’ 23-24 Perspektif Ibn Kathīr dan M. Quraish Shihab - Fauzi Fathur Rosi; Noer Halimah Asyihabi (Kuras Institute, 2024)
In contemporary society, children's neglect in treating their parents properly is increasingly observed. Filial piety, ranking just below the obligation to worship Allah SWT, is essential and extends universally beyond Muslim parents. This research aims to: 1) Analyze the interpretation of Al-Walid according to Ibn Kathīr and M. Quraish Shihab, and 2) Identify differences and similarities in their exegesis of Surah Al-Isra, verses 23-24. Using qualitative library research, primary sources include the tafsir works of Ibn Kathīr and Al-Mishbah by M. Quraish Shihab, along with related journals, articles, and books. Findings reveal: 1) The commandment to worship Allah SWT exclusively, and 2) The obligation for children to show filial piety by avoiding harsh words, even mild expressions like